Estudo tomográfico da prevalência de cava cerebrais e de outras variantes neuroanatômicas em dois hospitais privados de Fortaleza – Ceará - Lisboa, Lia Pontes (2018)
Background: Anatomical variations supposedly do not have pathological significance. Among the intracranial variations, the persistence of brain Cava, specially Cavum Septum Pellucidum (CSP), exhibits great clinical relevance, because, despite being a quite common finding, it has been cited as a marker of brain dysgenesis. Besides Cava, some intracranial calcifications have a dubious significance in the literature, representing possible wrong diagnosis. Aims: This study sought to descriptively evaluate the prevalence of CSP, Cavum Vergae (CV) and Cavum velum Interpositi (CVI), as well as some intracranial calcifications and neuroanatomical variations, in brain computed tomographies (CTs) in two private hospitals in Fortaleza. Methods: Data of 1,016 Head CTs from Hospital 1 and 451 Head CTs from Hospital 2 were analyzed. Besides the presence of Cava and calcifications, other findings were also registered. Patients were divided into two groups: with and without traumatic brain injury (TBI). The prevalence of Cava and the other findings was assessed in both groups, among the Hospitals and the calcifications were classified considering the possibility of being related to neurocysticercosis (NCC). Results: Female predominance was found in both institutions and the female population was older than the male population. The most common reason ordering Head CT in the population was TBI. Except for CSP et Vergae and CSP (equally found in both hospitals), all types of Cava were more commonly found in Hospital 1. The most prevalent Cavum was the CSP. The presence of possible, probable or definitive NCC was higher in Hospital 1. Conclusion: The percentage of brain Cava found in our sample was similar to other tomographic studies around the world and it might be representative of the prevalence of Cava in the middle class of the Brazilian Northeast. There was a higher proportion of Cava in the group of patients with lower socioeconomic status, which, to the best of our knowledge, seems to be a novel data, emphasizing that lower socioeconomic status may be a risk factor for the development of cerebral Cava.